Abrasive Waterjet Texturing as a Method to Enhance the Embedment of Metallic Inserts in Composite Materials. (2015) - Artaza, T.; Alberdi, A.; Olite, J.; Latapia, J.L.; Gil, D.; Suarez, A.; Rivero, A.
Abstract: This research work arises from the need of embedding metals in composite materials to improve mechanical performance of adapted metal inserts for the union of rotor blades by improving the inertia, while strengthening and decreasing the total weight of the structure. The resin union itself or with adhesives is not enough to achieve the high requirements demanded by industries like boat industry, civil engineering, aerospace industry or wind sector, where high loads are commonly employed. This work proposes an innovative method to assure a rigid and secure embedment of the metallic insert, thus, avoiding problems related to the decoupling of the metal-composite interface. This method consists on generating a "mechanical restraint" by texturing the metallic surface by abrasive waterjet (AWJ) technology, which has demonstrated to be a flexible method to generate different textures in metallic surfaces. This paper presents the experimental work done in steel and fiberglass/epoxy laminate.